PENERAPAN METODE PEMBELAJARAN COOPERATIVE STAD UNTUK MENINGKATKAN HASIL BELAJAR - Lisna wati Luaha Lisna (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2024)
This researcher aims To find out whether the application of the Cooperative STAD learning method can improve the learning outcomes of class VIII students at SMP Negeri 3 Onolalu for the 2023 academic year.The Cooperative STAD learning mode is a group learning method where students who play a more active role learn from several topics that have been determined by the teacher which can improve student learning outcomes in studying social studies. This research was carried out at SMP Negeri 3 Onolalu with the research subjects being students in class VIII Semester 1 of the 2023 academic year, totaling 28 people consisting of 12 boys and 16 girls. The research method used is classroom action research (PTK). Each cycle consists of two meetings plus one meeting for giving a learning outcomes test. The research results from processing the percentage of student learning completeness in cycle were 71.4% complete and 28.6% incomplete. Meanwhile, the results of research in cycle II were 92.9% complete and 7.1% incomplete. The conclusion in this research is that the application of the STAD Cooperative learning method can improve students’ learning abilities in the teaching and learning process, student activity in the teaching and learning process without being in cycle II after implementing the STAD Cooperative learning method. The results of this research are the efforts of researches in collaboration with social studies subject teachersb At the research location, students’activeness in the teaching and learning process was visible in cycle II after implementing the STAD Cooperative Learning method Suggestions that can be given by researchers are (1) in carrying out the learning process, subject teachers should choose and apply learning models (2) teachers should use learning models that involve students actively during the teaching and learning process,(3) research results should be This will be a consideration for future researchers.